An ordered structured cathode based on vertically aligned Pt nanotubes for ultra-low Pt loading passive direct methanol fuel cells - Wang, Guoliang; Lei, L.; Jiang, J.; Zhou, Y.; Huang, Q.; Zou, Z.; Jiang, San Ping; Yang, H. (Pergamon, 2017)
© 2017 Ordered nanostructured cathodes based on controlled vertically aligned Pt nanotubes are fabricated via combining sacrificial template method and in-situ galvanic replacement for ultra-low Pt loading passive direct methanol fuel cells (DMFCs). The Pt nanotubes are composed of highly dispersed Pt nanoparticles shell with an average thickness of ca. 15 nm. Employed as the oxygen reduction reaction (ORR) electrocatalyst, it exhibits similar activity but better durability than that of the commercial Pt black. Serving as the cathode for passive DMFC, a high electrochemical specific area of 77.48 m 2 g -1 (Pt) is obtained by the ordered nanostructured cathode, which is 3 times higher than that of the conventional Pt/C based cathode (19.46 m 2 g -1 (Pt) ), indicating a significant improvement in the Pt catalyst utilization. Impressively, the Pt loading at the cathode side can be reduced to approximately 1/7 (0.12 mgcm -2 ) of the conventional MEA without sacrificing cell performance by using the vertically aligned Pt nanotubes catalytic layer. This method may provide a new way to fabricate ordered nanostructured cathode for ultra-low Pt loadings fuel cells.